2010
DOI: 10.1073/pnas.0908320107
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on anthropoid origins

Abstract: Adaptive shifts associated with human origins are brought to light as we examine the human fossil record and study our own genome and that of our closest ape relatives. However, the more ancient roots of many human characteristics are revealed through the study of a broader array of living anthropoids and the increasingly dense fossil record of the earliest anthropoid radiations. Genomic data and fossils of early primates in Asia and Africa clarify relationships among the major clades of primates. Progress in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 111 publications
6
77
0
Order By: Relevance
“…In the process of evolution, this has served as a competitive advantage, but at a great price: an extremely high metabolic turnover compared with tissue volume [15] that is managed well in young adults, but not in the aged, since becoming 60+ years old is new in an evolutionary perspective [1618]. In this in vivo study of humans, we found that aging was associated with a thinning of the photoreceptor layer and a thickening of the RPE-BM layer at the foveal minimum.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of evolution, this has served as a competitive advantage, but at a great price: an extremely high metabolic turnover compared with tissue volume [15] that is managed well in young adults, but not in the aged, since becoming 60+ years old is new in an evolutionary perspective [1618]. In this in vivo study of humans, we found that aging was associated with a thinning of the photoreceptor layer and a thickening of the RPE-BM layer at the foveal minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Although their affinities are widely debated, most of the fragmentary early (Paleocene to mid-Eocene) fossils that have been proposed recently as candidate basal anthropoids (Eosimias, Algeripithecus, Biretia, Altiatlasius, Anthrasimias) exhibit some combination of diminutive size, moderately trenchant cheek teeth, and enlarged orbits, suggesting derivation from a small, visually predatory ancestor. 101,[108][109][110][111][112][113] Can we then still attribute the origin of the distinctive euprimate traits to a basal adaptive shift involving visually directed predation? I am now inclined to think that the whole notion of a defining adaptive shift that accounts for ''primate origins'' is another hallucination born of ignorance.…”
Section: Primate Origins?mentioning
confidence: 99%
“…Accordingly, tarsiers are not only allocated to their own family (Tarsiidae) and superfamily (Tarsioidea), but also to their own infraorder (Tarsiiformes). Debate over the phyletic position of tarsiiformes is longstanding [3], but recent phylogenies have unequivocally united tarsiers with anthropoid primates (monkeys, apes and humans) in the semiorder Haplorhini [4,5]. Thus, the functional and behavioural ecology of tarsiers has the potential to inform hypotheses focused on the origin of anthropoid primates [6].…”
Section: Introductionmentioning
confidence: 99%
“…The consensus view-that stem haplorhines were diurnal and that this heritage is partly obscured by a reversion to nocturnality in tarsiers [3]-helps account for one of the most striking aspects of the tarsier visual system: their outsized eyes (figure 1b; [6]). It has long been suggested that the extreme ocular hypertrophy of tarsiers is related to the absence of a tapetum lucidum (the structure that results in the phenomenon of 'eye shine'; [14]).…”
Section: Introductionmentioning
confidence: 99%